Taxation, foreign aid and political governance in Africa - Simplice A. Asongu; Nicholas M. Odhiambo (The European Journal of Comparative Economics, 2021)
This study examines the hypothesis that foreign aid dilutes the positive role of taxation on political governance. The empirical evidence is based on the Generalised Method of Moments and 53 African countries for the period 1996-2010. For more policy options, the dataset is disaggregated into fundamental characteristics of African development based on income levels, legal origins, natural resources and landlockedness. While the hypothesis is invalid in baseline Africa, low income and English common law countries of the continent, the research cannot conclude on its validity for other fundamental characteristics of development. Policy implications, caveats and directions for future research are discussed.